2010
DOI: 10.29333/ejgm/82850
|View full text |Cite
|
Sign up to set email alerts
|

Subnasale to Gnathion Distance and Nasal Index of Children with Homozygous Sickle Cell Disease in Port-Harcourt

Abstract: Aim:This study is designed to determine changes in some of craniofacial parameters such as subnasale to gnathion distance and nasal index in sickle cell anaemia in comparison to the healthy children in Port-Harcourt. Method: In this research which span over a two year period, measurements were taken of the facial indices (nasal and the subnasale to gnathion distances) of 100 confirmed homozygous (SS) children who attended the Sickle cell clinic of the University of Port Harcourt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This fi nding does not tally with fi ndings of previous researchers that reported the mesocephalic head shape as dominant among sickle cell patients. 5 Head circumference values were found to be higher in sickle cell disease children (mean OFC=48.89±3.15) than in normal growing non-sickle cell disease children (mean OFC=44.97±6.07). This fi nding agrees with previous study that reported a higher head circumference in sickle cell anemia children as compared to that of normal growing children.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This fi nding does not tally with fi ndings of previous researchers that reported the mesocephalic head shape as dominant among sickle cell patients. 5 Head circumference values were found to be higher in sickle cell disease children (mean OFC=48.89±3.15) than in normal growing non-sickle cell disease children (mean OFC=44.97±6.07). This fi nding agrees with previous study that reported a higher head circumference in sickle cell anemia children as compared to that of normal growing children.…”
Section: Discussionmentioning
confidence: 97%
“…26 Diploic thickening is signifi cant in only the frontal and parietal regions with little involvement of the squamous part of temporal or occipital bone, giving the sickle cell disease patient a lower cranial index. 5 Although, diploic thickening is non specifi c for the sickle cell disease skull as it is also a feature in other anemia related conditions such as severe iron defi ciency, thalassemia. 27 Growth defi cit tends to be greater in width than in height or length and is more severe in patients with sickle cell anemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] Gnathion was marked as the most inferior midline point on the mandible. [12] Measurements were made from nasion to gnathion and recorded in millimeters using vernier calipers [Figure 1]. Facial width was recorded as the distance between the zygomatic arches using bow callipers[13] [Figure 2].…”
Section: Methodsmentioning
confidence: 99%